Formulary Selection Criteria for Biosimilars: Considerations for US Health-System Pharmacists. Issue 9 (October 2014) - Griffith, Niesha; McBride, Ali; Stevenson, James G.; Green, Larry
Pharmacists will play a key role in evaluating biosimilars for formulary inclusion in the United States. As defined by US law, a biosimilar is a biologic that is highly similar to its reference product, notwithstanding minor differences in clinically inactive components, and should not have clinically meaningful differences from its reference product in safety, purity, and potency. We review biosimilars and the current European Union and US regulatory pathways for biosimilars. Furthermore, we propose a checklist of considerations to ensure that US pharmacists thoroughly evaluate future biosimilars for formulary inclusion. Included in the checklist are considerations related to the availability of preapproval and postapproval safety and efficacy data; differences in product characteristics and immunogenicity between the biosimilar and reference product; manufacturer-related parameters that can affect a reliable supply of quality products; health-system and patient perspectives on product packaging, labeling, storage, and administration; costs and insurance coverage; patient education; interchangeability and differences in the range of indications; and evaluation of institutions' information technology systems.